Activation of retinal microglial cells is not associated with Müller cell reactivity in vitrectomized rabbit eyes. (31st August 2012) - Ulbricht, Elke; Pannicke, Thomas; Uhlmann, Susann; Wiedemann, Peter; Reichenbach, Andreas; Francke, Mike
Abstract: Purpose:  Vitrectomy is a frequently performed surgical intervention in ophthalmology to remove vitreous traction and opacities or to treat complicated retinal detachments and diabetic changes. However, there is lack of information about cellular responses in retinal tissue after a surgical intervention such as vitrectomy. Microglia cells, the immune competent cells of neuronal tissue, are involved in nearly all neuropathological changes and are additionally activated by neurosurgical interventions. For most neurodegenerative changes, it is described that microglia activation is generally accompanied by a reactive gliosis of macroglial cells. However, it is not known whether microglial cell activation is necessarily associated with macroglial cell gliosis or whether these processes are regulated separately. Furthermore, there is an ongoing debate about possible detrimental consequences of microglial cell activation for neurons in central neural and retinal tissue. Methods:  Using immunohistochemistry and whole‐cell patch clamp experiments in a rabbit model of partial pars plana vitrectomy, we investigated micro‐ and macroglial cell reactivity after this intervention. Results:  Partial vitrectomy induced a massive microglia response characterized by morphological changes, intraretinal migration and proliferation of retinal microglial cells, respectively. Microglial cell reactivity was observed 2 days after the operation and was down‐regulated after 7 days. Microglia reactivity was associated with neither a general Müller cell gliosis nor an obvious neuronal cell loss. Electrophysiological examinations revealed no significant changes of whole‐cell currents and membrane potentials of Müller cells from healthy and vitrectomized eyes up to 3 weeks after operation. Only a small number of individual Müller glial cells expressed GFAP or reduced their inward currents as a sign of Müller cell gliosis. Conclusion:  Vitrectomy induced a massive response of microglial cells. However, microglia activation and deactivation are effectively regulated and are not necessarily associated with macroglial (Müller) cell reactivity and with obvious detrimental effects to neurons.